The Communism of Science - Anonymous (Online Ethics Center, 2006)
Discussion of who owns data, fairness in alab and doing controversial and difficult work.
Case Study / Scenario|Hypothetical / Fictional Case
Keywords: Authorship; Collaboration; Data Management; Mentors and Trainees; Publication Ethics; Research and Practice